Statue of Sir Pherozeshah Mehta - Ghosh, Ayan (2023)
A prominent member of the Parsi community in Bombay, Sir Pherozeshah Mehta drafted the Bombay Municipal Act of 1872 and is thus considered the 'Father of Bombay Municipality'. He became municipal commissioner of Bombay Municipality in 1873 and its president four times—1884, 1885, 1905 and 1911. A statue of Sir Pherozeshah Mehta was installed in front of the BMC building in honor of his role in the establishment of the municipality.